Predictors of oral hygiene practices among primary school children of Alzintan City, Libya - N. A., Al Trabelsi; Juni, Muhamad Hanafiah; Zainuddin, Huda (Community Health Society Malaysia, 2015)
Background: Good oral health is essential for the well-being and development of young children. Preservation of good oral hygiene in children is important for the development of strong, healthy teeth and to decrease the possibility of dental caries. Oral health is maintained by regular eating and drinking, as well as daily mechanical and pharmacological cleaning of the mouth, for example, brushing teeth with fluoride toothpaste and flossing. The aim of the study is to determine oral hygiene practices among public primary school children in Al Zintan City, Libya.